Mobile-Assisted Language Learning (MALL) Innovation for Vocational Education - Adijaya, Made Aryawan; Armawan, I Ketut; Kristiantari, Maria Goreti Rini (International Journal of Language Education, 2023)
Learning activities need to facilitate vocational students in learning independently. It certainly has an impact on students' low understanding and skills. This research aims to develop Mobile-Assisted Language Learning (MALL) for Vocational Education. This type of research is development research. The development model used is the ADDIE model. The subjects of this research consisted of 2 learning design experts, 2 learning media experts, and 2 learning materials experts, as well as practical tests carried out by 2 teachers. Individual trials were carried out on 3 students, and small group trials were carried out on 12 students. Data collection methods are observation, interviews, and questionnaires. The instrument used is a questionnaire. The data analysis techniques for this research are qualitative descriptive analysis and quantitative descriptive analysis. The results of the research, namely the assessment given by learning material experts, obtained an average of 96.5%. It was concluded that the MALL developed had very valid qualifications. The results of the learning media expert assessment were 97%, so the qualification was very valid. The results of the assessment given by the teacher were an average of 96%. The results of individual trials were 95.6%, and small group results were 94.7% (very good). It was concluded that the mobile-assisted language learning (MALL) developed had very good and practical qualifications, so it was suitable for use in English language learning.